In Situ Monitoring of DNA‐Aptavalve Gating Function on Mesoporous Silica Nanoparticles. (21st December 2013) - Özalp, Veli C.; Pinto, Alessandro; Nikulina, Elizaveta; Chuvilin, Andrey; Schäfer, Thomas
<x xml:space="preserve">Abstract</x> Mesoporous silica nanoparticles have proved to be efficient stimuli‐responsive controlled release systems for drug delivery when functionalized with nanovalves. Nucleic acid aptamers have recently been adapted to function as novel nanovalves, so‐called "aptavalves, " with molecular‐recognition capabilities and target concentration‐dependent actuation in nanopore‐controlled drug delivery and membrane separation systems. The working mechanism of aptavales relies on their structural rearrangement triggered by a specific target molecule. As a consequence, a controlled and concentration‐dependent release of payload occurs rendering this system particularly appealing for therapeutic applications. However, straightforward monitoring techniques are necessary in order to elucidate the function of aptavalves in situ and varying experimental conditions. Here, the structure‐switching mechanical movements of an ATP‐responsive aptavalve on the surface of mesoporous silica are characterized in real‐time and in situ using circular dichroism (CD). The experimental data obtained on the aptavalve actuation are in excellent agreement with the payload release kinetics determined by fluorescence measurements. It is shown that CD serves as a reliable real‐time analysis of the function of aptalvalves, and that the results obtained obey furthermore standard controlled release models. This allows in principle to pre‐determine the release rate of the modified silica particles according to particular application requirements.